MENGGALI FAKTOR PSIKOLOGIS KEPATUHAN PAJAK: PERAN LITERASI DAN PERSEPSI TARIF PAJAK - Dhiva Ismi Fauziah; Antin Okfitasari; Ety Meikhati (JURNAL ILMIAH EDUNOMIKA, 2025)
Tax compliance, a major challenge in Indonesia, is influenced by various psychological factors. This study aims to examine the influence of tax literacy and perceptions of tax rates on taxpayer compliance at the Surakarta Tax Office (KPP Pratama). Using a quantitative approach, questionnaire data were collected from 100 individual and corporate taxpayers through purposive sampling and analyzed using multiple linear regression. The results indicate that both tax literacy and perceptions of tax rates partially have a positive and significant effect on compliance. Simultaneously, these two variables are proven to be strong predictors of taxpayer compliance. This study concludes that internal factors, namely taxpayers' personal understanding and evaluation, are fundamental drivers of compliance. Therefore, this study recommends that the Direktorat Jendral Pajak (DJP) prioritize educational programs to improve literacy and transparency to shape positive public perception. Future research is recommended to integrate other psychological variables, such as social norms, to develop a more comprehensive exposure model.